Association between fentanyl use and reduced risk of tension pneumothorax in extremely preterm infants born at 22–23 weeks' gestation: a retrospective case–control study - Kurimoto, Tomonori; Takuya, Tokuhisa; Ohashi, Hiroshi; Hirakawa, Eiji; Kibe, Masaya; Maeda, Takatsugu; Kamitomo, Masato (Frontiers in Pediatrics, 2025)
BackgroundTension pneumothorax is a life-threatening complication in extremely preterm infants, especially within the first 72 hours of life. Identifying preventive strategies is crucial to improving survival rates. This study aimed to evaluate the association between fentanyl use and the incidence of tension pneumothorax in extremely preterm infants born at 22–23 weeks of gestation.MethodsThis retrospective case–control study was conducted at a tertiary care center in Japan. It included 138 preterm infants with a gestational age from 22 weeks + 0 days to 23 weeks + 6 days (January 2010 to March 2023). Logistic regression and propensity score matching were used to adjust for confounding factors such as chorioamnionitis stage 2–3, oligohydramnios, antenatal steroids, ventilation mode, persistent pulmonary hypertension, and birth at a primary or secondary perinatal center.ResultsSixteen infants (11.6%) developed tension pneumothorax within 72 h of birth, with a mortality rate of 68.7%. The use of fentanyl was associated with a reduced risk of tension pneumothorax (adjusted odds ratio: 0.1; 95% confidence interval: 0.01–0.75).ConclusionThe use of fentanyl may reduce the risk of tension pneumothorax within the first 72 h of life in infants born at 22–23 weeks of gestation. Further randomized controlled trials are needed to validate these findings and assess long-term outcomes.